'Know thyself' – host factors influencing cancer response to immune checkpoint inhibitors. Issue 4 (20th May 2022) - Gunjur, Ashray; Manrique‐Rincón, Andrea J; Klein, Oliver; Behren, Andreas; Lawley, Trevor D; Welsh, Sarah J; Adams, David J
Abstract: Immune checkpoint inhibitors (ICIs) have revolutionised oncology and are now standard‐of‐care for the treatment of a wide variety of solid neoplasms. However, tumour responses remain unpredictable, experienced by only a minority of ICI recipients across malignancy types. Therefore, there is an urgent need for better predictive biomarkers to identify a priori the patients most likely to benefit from these therapies. Despite considerable efforts, only three such biomarkers are FDA‐approved for clinical use, and all rely on the availability of tumour tissue for immunohistochemical staining or genomic assays. There is emerging evidence that host factors – for example, genetic, metabolic, and immune factors, as well as the composition of one's gut microbiota – influence the response of a patient's cancer to ICIs. Tantalisingly, some of these factors are modifiable, paving the way for co‐therapies that may enhance the therapeutic index of these treatments. Herein, we review key host factors that are of potential biomarker value for response to ICI therapy, with a particular focus on the proposed mechanisms for these influences. © 2022 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.